(untitled) (American Journal of Islam and Society, 2000)
History, or more properly the writing of history, had been during the times of the ancient Greeks and Romans an elitist activity, meant for glorifying the class of power, position, and birth. Parts of these histories were fabulous in nature. The Muslims (Arabs) introduced the idea of history as factual record. During the Middle Ages, history writing slipped into what it was in the Greco-Roman times. In the 16th century, the middle class, those with accumulated capital, wrote histories. A colonial history, too, developed, enshrining a Euroean view of history that still continues in school curricula. The 20th century saw changes. The writing of history became an imperialist necessity. When imperialism collapsed, the focus disappeared. History became miniaturized and atomized. The entry of television and information technology brought instant histories. Islamic history writing accepts history as an instrument of Allah’s will and mode of living the good life.